Implementación de una contabilidad comercial en el almacén Ferrotec de la ciudad de Loja, durante el período julio - septiembre 2016. - Jumbo Sanambay, Mayra del Carmen (2018)
The present investigative work was carried out in order to provide a fundamental tool for the adequate economic development of the FERROTEC hardware store, whose objective is aimed at the benefit of the business and therefore meet the needs of its customers. It is also done, as a prerequisite to obtain the degree in Accounting and Auditing CPA., According to Article 129 of the Regulation of Academic Regime of the National University of Loja. In compliance with the objectives set out in this thesis, a logical and orderly order was followed, which starts with the registration of purchases, sales and retentions, followed by the Accounts Plan, Initial Situation Status; the Memorandum of operations, in a period of two months, to proceed to analyze and elaborate the accounting entries in the Daily Book, whose values are transferred to the Major General and their balances to the Balance of Verification, Worksheet, the respective Adjustments and finally all the this information in the Financial Statements. With the results obtained, it was concluded that the owner of "FERROTEC" does not maintain a clear accounting system, which helps the economic management of the same, which does not allow an adequate record of the transactions that occur every day, to obtain the Financial Statements and reliable tax obligations. Finally, it is recommended that the owner consider the present work developed in this thesis, in order to have timely and reliable economic information for the correct decision making in benefit of its development.